Monoalkylated Epigallocatechin-3-gallate (C18-EGCG) as Novel Lipophilic EGCG Derivative: Characterization and Antioxidant Evaluation - Cristina Minnelli; Roberta Galeazzi; Emiliano Laudadio; Adolfo Amici; Dario Rusciano; Tatiana Armeni; Mattia Cantarini; Pierluigi Stipa; Giovanna Mobbili (MDPI AG, 2020)
Epigallocatechin-3-gallate (EGCG) has the highest antioxidant activity compared to the others catechins of green tea. However, the beneficial effects are mainly limited by its poor membrane permeability. A derivatization strategy to increase the EGCG interaction with lipid membranes is considered as one feasible approach to expand its application in lipophilic media, in particular the cellular absorption. At this purpose the hydrophilic EGCG was modified by inserting an aliphatic C18 chain linked to the gallate ring by an ethereal bond, the structure determined by NMR (Nuclear Magnetic Resonance) and confirmed by Density Functional Theory (DFT) calculations. The in vitro antioxidant activity of the mono-alkylated EGCG (C18-EGCG) was studied by the DPPH and Thiobarbituric Acid Reactive Substances (TBARS) assays, and its ability to protect cells towards oxidative stress was evaluated in Adult Retinal Pigmented Epithelium (ARPE-19) cells. Molecular Dynamics (MD) simulation and liposomal/buffer partition were used to study the interaction of the modified and unmodified antioxidants with a cell membrane model: the combined experimental-in silico approach shed light on the higher affinity of C18-EGCG toward lipid bilayer. Although the DPPH assay stated that the functionalization decreases the EGCG activity against free radicals, from cellular experiments it resulted that the lipid moiety increases the antioxidant protection of the new lipophilic derivative.